Fulminant Acute Disseminated Encephalomyelitis: A Remarkable Outcome with Cyclophosphamide - Meirson, Hadas; Shiran, Shelly I.; Raz, Michal; Roth, Jonathan; Fattal-Valevski, Aviva (Journal of Pediatric Neurology, 2020)
Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the central nervous system which occurs predominantly in the pediatric population. Acute treatment is high-dose intravenous glucocorticoids. Alternative treatment is usually intravenous immune globulin and/or plasma exchange. Fulminant ADEM is rare in children. Only a few cases of cyclophosphamide use in refractory ADEM have been reported. Here, we report a case of a 12-year-old girl with fulminant ADEM who was comatose and improved dramatically after cyclophosphamide administration. Cyclophosphamide treatment should be considered as a therapy in children with fulminant ADEM nonresponsive to standard therapies.
Keywords: acute disseminated encephalomyelitis; intravenous immune globulin; cyclophosphamide